Comparative Analysis of Islamic Banks’ Performance in Indonesia and Malaysia with RGEC and the Islamicity Performance Index (2018-2021) - Tata Fatima Azzahra; Muhammad Sholahuddin; Soepatini Soepatini (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
Using the RGEC (Risk Profile, Good Governance, Profit, Capital) method for measuring financial performance and the Islamicity Performance Index (IPI) for measuring Shariah performance, this study seeks to identify differences in the performance of Islamic banks in Indonesia and Malaysia for the period from 2018-2021. Target sampling was used to select the sample, which consisted of secondary data from two Islamic banks in Indonesia and two Islamic banks in Malaysia from the banks’ 2018-2021 annual reports. Financial ratio analysis and various test analyses using the non-parametric Mann-Whitney U method are used as analytic methods. According to the statistical calculations of the RGEC method, there is no difference in the average values of NPF, GCG, ROA, and BOPO, but there is a difference in the average values of FDR, ROE, NI, and CAR between Bank Syariah Indonesia and Bank Syariah Malaysia. The IPI method reveals that the average values of PSR, ZPR, EDR, and the ratio of Islamic Income vs non-Islamic Income recorded differences in average value, and the ratio of Islamic Investment vs non-Islamic Investment demonstrates that there is no difference between the average scores of Indonesian Shariah Banks and Malaysian Shariah Banks.